Rancang Bangun Mesin Pengayak Pasir Sistem Rotary Dengan Tiga Grade Hasil Ayakan - Agus Wijianto; Wahyu Wardana (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2023)
Sand is the main ingredient in the construction process, so based on its function, size separation is needed. This size separation is done by sifting sand. Based on the survey, many construction or industrial workers use traditional methods of sifting sand, and the results obtained are less effective in terms of capacity and working time.The rotary system sand sieving machine is planned as a tool to make it easier to sift sand. The sifter tube is designed with 2 sieves. The first filter uses a mesh size 6 and the second filter uses a mesh size 8. This is done to produce 3 grades of sand.This rotary system sand sifter machine aims to sift sand with 3 different sieve results, namely fine sand, medium sand, and gravel. Fine sand is used as a mixture of plaster for concrete walls, medium sand is used as a mixture in bricklaying, and gravel is used as a mixture of foundation casts. In the mechanical movement system using a 1 Hp AC motor as a source of rotation, then the rotation of the motor is transmitted through a reducer with a ratio of 1:40 and then forwarded to the shaft. On the shaft there is a filter for sifting the rotary system sand.This research was conducted with 3 variations of the angle of the sieve which is 10°, 15°, 20°. In testing the maximum capacity in one test is 30 kilograms. The best sieve results were obtained from testing with a 10° sieve angle using dry river sand and dry land sand.